Flexibilización sin precarización: estrategias para prevenir la precarización en la era de la modernización económica - Camacho Ramírez, Adriana (2023)
The prevailing economic policy in the world has led, without intending to do so, to the impoverishment of many social groups and, consequently, to the violation of economic and social rights in many countries. Economic modernization has sought to protect economic capital (employers) more than human capital (employees), without realizing the negative repercussions that this confrontation brings to society. Labor market flexibilization, a consequence of economic modernization, has become e quivalent to job insecurity, or precarious work. The great challenge we face is to reconcile the protection and stability of workers with economic policies and corporate profits